High Pressure and Long Compression Improve the Quality of Coffee Waste Biopellets : Tekanan Tinggi dan Kompresi Lama Meningkatkan Kualitas Biopellet Limbah Kopi - Nurzati, Syarif Adhika Adhin; Rhakasywi, Damora; Fahrudin, Fahrudin (Indonesian Journal of Innovation Studies, 2025)
General Background The increasing demand for renewable energy highlights the potential of biomass waste as a sustainable energy source. Specific Background Spent coffee grounds represent an abundant biomass material with high calorific potential, yet their utilization efficiency depends strongly on processing parameters during pelletization. Knowledge Gap Previous studies have not fully elucidated how compaction pressure and pressing duration affect the physicochemical characteristics of coffee-ground biopellets according to the SNI 8021:2014 standard. Aims This study investigates the effects of varying pressure (500, 750, and 1000 kgf) and pressing duration (30 s and 180 s) on the quality attributes of biopellets composed of 92.5% coffee waste and 7.5% tapioca adhesive. Results Findings indicate that higher pressure and longer pressing duration significantly improve density, reduce moisture and volatile matter, and enhance fixed carbon content, though the ash content remains above the acceptable limit. The optimal combination of 1000 kgf and 180 s produced biopellets meeting the SNI standards for calorific value and bound carbon. Novelty This research provides quantitative insights into the synergistic role of mechanical compaction and pressing time in optimizing biofuel quality from coffee waste. Implications The results support the advancement of circular bioenergy production in Indonesia by transforming coffee waste into high-quality renewable fuel. Highlights: High pressure and longer compression improve biopellet quality. Only 1000 kgf–180 s meets SNI standards for bound carbon and calorific value. High ash content remains the main limitation of coffee waste biopellets. Keywords: Biopellet, Coffee Waste, Pressure, Compression Time, Renewable Energy